One mean ant - Yorinks, Arthur (Candlewick Press, 2020)
"Was there ever an ant as mean as this mean ant? Not likely. This ant is so mean that leaves fall off trees when he walks by. This ant is so mean that grapes shrivel when he looks at them. But when this mean ant finds himself lost in the desert and meets a fly that defies explanation . . . well, nothing is the same again. With this first in a planned trilogy, celebrated picture book creators Arthur Yorinks and Sergio Ruzzier team up for a hilariously slapstick tale that will make a raucous read-aloud for any storytime."--Provided by publisher.